2020
DOI: 10.1088/1755-1315/575/1/012205
|View full text |Cite
|
Sign up to set email alerts
|

Conflict as a negotiation strategy of society around mining activities

Abstract: This paper aims to examine the conflicts that occur between communities around the mine and mining companies. Mining is one sector that often reaps protests that lead to conflicts from communities other than plantations and forestry. Conflicts that occur in the same form tend to be resolved through the same method. Conflicts that occur repeatedly indicate there is no conflict resolution for the substantial problem that was become the conflict trigger. Conflict resolution efforts are often not directly related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Regional income ideally follows Indonesia Law Number 28/2009 regarding local taxation and charging [56]. RA, normatively, brings efficiency, transparency, and accountability in governing people and attracts business; unfortunately, numerous studies have shown that these local regulations are counterproductive in some aspects, including for the agricultural sector and environment [57][58][59], particularly in the forestry sector [60,61].…”
Section: Overview Of Decentralization/regional Autonomy (Ra) and Pres...mentioning
confidence: 99%
“…Regional income ideally follows Indonesia Law Number 28/2009 regarding local taxation and charging [56]. RA, normatively, brings efficiency, transparency, and accountability in governing people and attracts business; unfortunately, numerous studies have shown that these local regulations are counterproductive in some aspects, including for the agricultural sector and environment [57][58][59], particularly in the forestry sector [60,61].…”
Section: Overview Of Decentralization/regional Autonomy (Ra) and Pres...mentioning
confidence: 99%
“…The lack of adherence to international standards of good practice from either side may quickly turn into actual conflict. Conflicts, indeed, surround a substantial number of mining operations, where the parties involved show little interest in building mutually beneficial agreements (Sukri et al, 2020).…”
Section: The Challenges Of the Mining Industrymentioning
confidence: 99%
“…Moreover, the environment in the region is threatened by huge direct and/or indirect impacts on the whole ecosystem. Some are very common and evident in mining areas such as land changes [45,49], destruction of grasslands [19,50], rivers and sources pollution [51], destruction of agricultural areas, and the decrease of its productions [46,52], and so on, negatively affecting the means of subsistence of the populations, causing the scarcity of certain essential resources (water, food) and degrading (decreasing) the quality of life in the whole region. This statement on the tensions surrounding conflicts linked to mining activities has been mentioned by the community leader in Kolaboui and reported by PACV as following:…”
Section: For Bauxite Mining Boxing Sites: To Whom Is the Faultmentioning
confidence: 99%